Using technology to improve civil service talent. - Kerr, Walter; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Civil service reform is highly complex and technology can serve a vital function. The brief provides a starting point for improving the management of civil services through technology in the region. Yet, it also emphasizes that countries must work with experts in civil service reform and technology to identify solutions that would be most useful and relevant for their needs.
Keywords: Public administration; Information technology; Electronic book